The Implementation of the Arba’in Method in Qawa’id Learning To Enhance Student Learning Performance - Aini, Kartika Mahya Nurul; Annas, Azwar (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2025)
Purpose- This study aimed to implement the Arba’in method in qawaʿid learning to bring significant improvement in students’ Arabic language acquisition at MTs Ibtidaul Falah Dawe, Kudus.  Design/Methodology/Aproach- This research used a descriptive qualitative methods, with the researcher serving as the primary instrument. The data included both primary and secondary sources. Data analysis was conducted in four stages: data collection, data reduction, data presentation, and conclusion drawing or verification.  Finding- The study showed that the Arba’in method helped students learn Arabic, particularly in understanding grammar. This method provided a more structured learning process through the use of a textbook incorporating mind mapping techniques.  Reseah Limitation/Implications- This study examined the application of the Arba’in method in teaching qawʿid at MTs Ibtidaul Falah Kudus. The findings were specific to this educational context and may not be applicable to other institutions. The participants were seventh-grade students in the 2024/2025 academic year. The study relied on a descriptive qualitative method involving observation and interviews. The results might have been influenced by the perspectives of both the researcher and the respondents. The time and location of the study could also have affected the context and outcomes.